Analisis Ukuran Partikel Nanosilica Pada Proses Alkali Fusion Silica Scaling Geotermal Dieng Menggunakan KOH - Waziz, Wildan; Fitriani, Fajar; Riko Aulia , Rachman (Journal of Mechanical Engineering, 2024)
One of the characteristics of the Dieng geothermal field is the high silica content in the production fluid which causes the appearance of silica scaling. The presence of silica scaling inhibits the energy extraction process and becomes waste that disturbs the environment. The silica scaling can be utilized as a nanosilica product for use as a reinforcing filler. Nano-sized powder is expected to improve the mechanical properties of a product with denser results. This research aims to synthesize nanosilica from geothermal scaling silica using the alkali fusion method. Nanosilica is obtained by reacting alkali KOH with silica scaling which has been reduced in size using ball milling. The fusion process is carried out using heat treatment at varying temperatures of 400, 450 and 500ºC. The fusion results were dissolved in distilled water for titration using 2M HCl with stirring using a magnetic stirrer until gelation was formed which was dried into silica nanoparticles. Characterization of the size of nanosilica powder using the Particle Size Analyzer (PSA) obtained the smallest size data at a fusion temperature of 400ºC with the size tending to increase as the fusion temperature increased, where these results were in line with the analysis of nanosilica images from Transmission Electron Microscopy (TEM) testing using ImageJ software. Compound analysis using Fourier Transform Infra-Red (FTIR) shows the presence of characteristic silica bonds. The results of X-Ray Diffraction (XRD) do not show sharp peaks so the compound has an amorphous phase.